(untitled) (Journal of Medicine, 2009)
Cholesterol ester storage disease (CESD) is a rare autosomal recessive disorder resulting from lysosomal acid lipase deficiency and is usually characterized by hepatomegaly and hyperlipidemia. It is diagnosed by liver biopsy which characteristically shows microvesicular steatosis and periportal fibrosis. Here we report a fourteen years old boy who had presented with unexplained hepatomegaly, and hyperlipidemia determined incidentally. He was finally diagnosed as a case of cholesterol ester storage disease by liver biopsy. Though there is yet no specific treatment for CESD; however, the early detection of cases would make the timely control of complications possible. Keyword: Cholesterol Ester Storage Disease, Lysosomal Storage Diseases, Lipidoses doi: 10.3329/jom.v10i2.2835 J MEDICINE 2009; 10 : 146-148